Waiver of Attorney in Juvenile Court, Massachusetts and Virginia, 2014-2018 - Woolard, Jennifer L. ([Verlag nicht ermittelbar], 2022)
The goal of this study is to examine age-based differences in knowledge and beliefs regarding the role of counsel, presumptions about counsel, and maturity of judgement when making decisions about whether to waive the right to counsel or the right to trial in a plea context. The study extends existing limited work on age-based differences in knowledge and decision making in several ways that improve ecological validity. The study examines knowledge, beliefs, and decisions among parent-youth pairs from the same family. This sampling strategy more closely approximates the real-life circumstances of waiver of counsel in which knowledge, beliefs, and decisions are nested and tested within family units. The dyadic analysis can offer insight into the challenges and opportunities that face youthful defendants at these critical junctures in case processing. It provides information about whether parents and youth understand these rights and whether assumptions that parents compensate for youths' lack of knowledge is reasonable.